2020
DOI: 10.3390/ijerph17134807
|View full text |Cite
|
Sign up to set email alerts
|

Everyday Pedelec Use and Its Effect on Meeting Physical Activity Guidelines

Abstract: Pedelecs (e-bikes with electrical support up to 25 km·h−1) are important in active transportation. Yet, little is known about physiological responses during their everyday use. We compared daily pedelec (P) and bicycle (B) use to determine if pedelecs are a suitable tool to enhance physical activity. In 101 employees, cycling duration and intensity, heart rate (HR) during P and B were recorded via a smartphone app. Each recording period was a randomized crossover design and lasted two weeks. The ride q… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…Respondents indicate that regular bikes that require physical effort are better for health and fitness than electric bikes. This is to some extent obvious, although as indicated in the research of [58][59][60][61], riding an electric bicycle also stimulates physical activity, thus providing health benefits.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Respondents indicate that regular bikes that require physical effort are better for health and fitness than electric bikes. This is to some extent obvious, although as indicated in the research of [58][59][60][61], riding an electric bicycle also stimulates physical activity, thus providing health benefits.…”
Section: Discussionmentioning
confidence: 99%
“…In this context, it is also extremely important to promote e-bikes as part of a strategy to reduce emissions [56]. Cycling, including electrically assisted cycling, increases, although to a lesser degree than conventional cycling [57], physical activity for daily commuting [58][59][60][61]. Despite its documented benefits, the increasing use of electric bicycles, and particularly the fact that the new users are new to any type of bicycle, poses a risk of accidents involving these vehicles [62].…”
Section: Literature Overviewmentioning
confidence: 99%
“…The sample size calculation was based on a previous feasibility study 24 among workers from companies located in the Hannover area. The study showed that 26% of cyclists reached the WHO criteria for physical activity.…”
Section: Methodsmentioning
confidence: 99%
“…Despite the electrical assistance evidence suggests that e-cycling is performed at at least a moderate intensity and leads to similar or slightly lower physical markers of intensity than conventional cycling (33). However, given that individuals report e-cycling for longer and more frequently than they do a conventional bicycle, e-cycling is often associated with greater weekly energy expenditure than a conventional bicycle (35,37).…”
Section: Introductionmentioning
confidence: 99%